2010
DOI: 10.1161/circep.109.917625
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hematoma Complications After Device Implant in the Clopidogrel Era

Abstract: Background-Device implant pocket hematoma is a recognized complication after permanent pacemaker (PM) and implantable cardioverter-defibrillator (ICD) implantation. Pocket hematoma is associated with local discomfort, an increased risk of infection, and may require surgical intervention or lead to lengthier hospital stays. The purpose of the study was to identify the clinical factors associated with hematoma formation after PM or ICD device implantation. Methods and Results-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 15 publications
(16 reference statements)
7
69
2
1
Order By: Relevance
“…1-3 Patients with cardiovascular disease are commonly being administered anticoagulation therapy using warfarin or the new oral anticoagulation drugs (NOACs), and antiplatelet therapy using aspirin and clopidogrel. [4][5][6][7] In particular, the data specific to CIED implantation significantly favor continuation of warfarin therapy through the procedure over bridging with heparin. 8, 9 In fact, continuing anticoagulation with warfarin does not increase the risk of hematoma compared with no anticoagulation.…”
mentioning
confidence: 99%
“…1-3 Patients with cardiovascular disease are commonly being administered anticoagulation therapy using warfarin or the new oral anticoagulation drugs (NOACs), and antiplatelet therapy using aspirin and clopidogrel. [4][5][6][7] In particular, the data specific to CIED implantation significantly favor continuation of warfarin therapy through the procedure over bridging with heparin. 8, 9 In fact, continuing anticoagulation with warfarin does not increase the risk of hematoma compared with no anticoagulation.…”
mentioning
confidence: 99%
“…A recent study reported that clopidogrel significantly increased the risk of pocket hematoma at the time of pacemaker or ICD implantation, and that its discontinuation >4 days before device implantation prevented development of hematoma. 16 The present study, however, highlights the perioperative management of anticoagulation, which seems to have more impact on major bleeding complications compared to antiplatelet therapy in patients undergoing ICD implantation ( Table 3).…”
Section: Discussionmentioning
confidence: 71%
“…Based on the prolonged efficacy of antiplatelet drugs, their use within 5 days of the operation was considered as ondrug antiplatelet treatment. 14, 16 Therefore, in the AP group, the discontinuation period of aspirin and thienopyridine (either clopidogrel or ticlopidine) before the procedure was variable (22) 22 (37) 21 (36) 13 (38) III 61 (22) 9 (7) 14 (24) 24 (40) 14 (41)…”
Section: Subjectsmentioning
confidence: 99%
“…Results from recent retrospective and prospective studies cite a wide range of estimates for the incidence of bleeding complications, ranging from 1.1% to 16% 7, 8, 9, 10, 11, 12, 13. Once bleeding occurs, clinically meaningful pocket hematoma has been linked to a significant increase in perioperative pain and decrease in quality of life 9.…”
Section: Introductionmentioning
confidence: 99%